Synthesis and structural study of azole containing cadmium-based metal organic frameworks for electrochemical detection of nitrobenzene - Mohamad Ishak, Nurul Nabihah (2019)
Metal organic frameworks (MOFs) represent a new class of porous crystalline materials which contains of organic linkers and inorganic joints. In particular, the synthesis of MOFs with nitrogen-rich ligands are extremely versatile materials. Nitrobenzene (NB) is a carcinogenic organic compound that is widely used in the manufacturing and chemical industries. The spill of industrial waste contain high level of NB can be harmful to human health. Hence, the development of MOFs as electrochemical sensors for determination of NB are essential. Three novel mixed ligand Cd(II) MOFs, namely MOF-717 (Cd(NO3)2.4H2O with 4,4’-oxybis(benzoic acid) (H2oba) and 3,5-diamino-1,2,4- triazole (Hdatrz)), MOF-718 (Cd(NO3)2.4H2O with H2oba and 3-amino-1,2,4- triazole (Hatrz) and MOF-719 (Cd(NO3)2.4H2O with 2,6-napthalenedicarboxylic acid (H2ndc) and Hdatrz) were successfully synthesised using solvothermal with 1 : 2 :2 molar ratio of Cd : L1 : L2 condition (L1 = H2oba/H2ndc and L2 = Hdatrz/Hatrz) at 120 °C. The compounds were characterised via Powder X-ray Diffraction (PXRD) analysis, Fourier Transform Infrared (FTIR), Nuclear Magnetic Resonance (NMR) spectroscopies, thermogravimetric analysis (TGA), Scanning Emission Microscopy (SEM), N2 physisorption analysis and the structural determination of MOFs was performed by Single-crystal X-ray Diffraction analysis (SXRD). The peaks at low angles in the PXRD pattern indicated the formation of large lattice unit cell of the frameworks. FTIR analysis shows reduction of C=O peaks intensity and this indicated the successful bonding of H2oba/H2ndc with Cd ions. NMR analysis confirmed the presence of both ligands in the frameworks. Thermal analysis indicated the MOFs had high thermal stability MOF 717 up to 450 ºC, MOF-718 up to 467 °C and MOF-719 up to 480 °C. MOF-717 and MOF-718 crystallised in a monoclinic system with C2/m space group showing three dimensional (3D) structure with fluorite (flu) topology. MOF-719 crystallised in a triclinic system with Pī space group showing a two dimensional (2D) underlayer structure and new topology. All the MOFs were modified with glassy carbon (GC) electrodes for electrochemical studies of nitrobenzene (NB) reduction using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. MOF- 717/GC electrode showed the highest electrocatalytic activity with a low detection limit (LOD) of 2.9 × 10-8 M and high sensitivity of 3.36 μA μM cm-2. This is due the present of active group of nitrogen and oxygen donor ligands from MOF-717 structures. This preliminary work indicated that these materials could be effective electrocatalysts in the electrochemical detection of the environmental pollutant NB.